2002
DOI: 10.3758/bf03196317
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of the DRM paradigm as a measure of individual differences in false memories

Abstract: Despite considerable researchon the Deese-Roediger-McDermott (DRM) false memory paradigm, little attention has been paid to the reliability of the paradigm as a measure of individual differences. In the present research, we examined the reliability of the DRM paradigm in a 2-week test-retest design. This analysis showed that the false memories produced in the paradigm were quite stable across the 2-week period and that this stability had both global (cross-list)and list-specificcomponents. In contrast, correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 33 publications
(56 reference statements)
2
25
0
Order By: Relevance
“…We believe the present results are also consistent with the Blair et al (2002) finding of substantial within-individual consistency in false recognition of critical lures from the same DRM lists tested two weeks apart, although Blair et al argued against response bias consistency as an account of their results (p. 595). Our conclusions seem at odds, however, with those of Salthouse and Siedlecki (2007), who did not find predictive relationships of false DRM recognition across tests differing in materials, nor reliable correlations between false recognition and established individual-difference variables.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We believe the present results are also consistent with the Blair et al (2002) finding of substantial within-individual consistency in false recognition of critical lures from the same DRM lists tested two weeks apart, although Blair et al argued against response bias consistency as an account of their results (p. 595). Our conclusions seem at odds, however, with those of Salthouse and Siedlecki (2007), who did not find predictive relationships of false DRM recognition across tests differing in materials, nor reliable correlations between false recognition and established individual-difference variables.…”
Section: Discussionsupporting
confidence: 81%
“…Blair et al (2002) reported a significant correlation between critical and noncritical false alarms on the first test, a result that hints at a relationship between general recognition bias and DRM false memories (although that correlation was not significant in the second test). Relatedly, Qin, Ogle, and Goodman (2008) found that response bias calculated from the noncritical DRM trials was significantly (albeit weakly) predictive of susceptibility to adopting fictitious childhood events as autobiographical.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mean false recognition rate for critical lures was 69.13% (N = 188), which is consistent with previous research (e.g., Blair, Lenton, & Hastie, 2002). Participants falsely recognized 14.63% (N = 20) of non-presented unrelated items.…”
Section: Recognition Ratessupporting
confidence: 80%
“…First, we can reasonably exclude a possible speculation about the reliability of false memory, because several previous studies suggested that DRM false memory is as much a reliable measure as DRM true memory (Blair, Lenton, & Hastie, 2002;Roediger, Watson, McDermott, & Gallo, 2001). Second, it is plausible that false memory is less heritable than true memory.…”
Section: Tablementioning
confidence: 99%